Report on proposed upgrading of Medan Kidd Ipoh intercity bus terminal for Majlis Bandaraya Ipoh at Ipoh Oldtown, Perak Darul Ridzwan / Mohamad Asyraf Mansor - Mansor, Mohamad Asyraf (2011)
In the final semester of Diploma of Interior Architecture, the students are required to come out with a project report based on the final project that the student is working on. My final project is proposed upgrading of Medan Kidd Ipoh Intercity Bus Terminal for Majlis Bandaraya Ipoh. The location of Medan Kidd is at Lot 13658, Off Jalan Tun Razak, Ipoh, Perak Darul Ridzuan. Medan Kidd was built in the year 1938 and the bus terminal is still operating till this day. It has become a centre for intercity bus route around Perak's state. It can accomodate more than 2000 users per day and had been operating along with several bus company such as General Omnibus Sdn Bhd, Ipoh Omnibus Sdn Bhd, Kinta Omnibus Sdn Bhd, and Reliance Co. Sdn Bhd. Medan Kidd had received a lot of complaints and reports due to the poor condition and the lack of facilities. As the years goes by, Medan Kidd had also grown old and problems started to sprung out bits by bits. Those problems that emerged is caused from the increase of users by each year and the upgrading service by the bus companies thus adding the number of buses that enters Medan Kidd. This has cause traffic flow problems, overcrowding and parking related issues. The old design are no longer able to circulate all the human traffic and vehicles flow smoothly. With the new design that offers solutions for all the problems, Medan Kidd is expected to be a new focal point in Ipoh city. Green design with a futuristic concept is applied to the new design scheme hence making a difference in the panoramic view of the town that are popular with the heritage architecture style. The new design scheme mainly focussed on improving and solving all the problems and issues that came from the previous design. In conclusion this proposal is a solutions for all the design issues and the new implied design to Medan Kidd will be a fresh scene for the environment and cityscape of Ipoh city.